2017
DOI: 10.18869/acadpub.nfsr.4.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity is Related to Women's Mental and Physical Health in Babolsar, Iran

Abstract: A B S T R A C TBackground and Objectives: Food insecurity has some adverse effects on health. Studies show that, there is a significant relationship between poor mental and physical health and food insecurity among low-income households. The purpose of this study is to investigate the relationship between household food insecurity and physical and mental health in Iranian women with high school age children. Materials and Methods:This cross-sectional study was conducted on 289 women with high school aged child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…For example, in a study conducted in June/July 2020 in the United States, low-income participants who had food insecurity were more than three times more likely to be at risk of depression and anxiety (Fang et al, 2021 ). Similar patterns were also observed prior to the pandemic where food insecurity has been linked to mental and physical disorders (Ramezani et al, 2017 ) . In a study based on an econometric analysis, hunger correlated with “worsening health” in a cohort of South Africans ( Nwosu et al, 2022 ) .…”
Section: Discussionsupporting
confidence: 71%
“…For example, in a study conducted in June/July 2020 in the United States, low-income participants who had food insecurity were more than three times more likely to be at risk of depression and anxiety (Fang et al, 2021 ). Similar patterns were also observed prior to the pandemic where food insecurity has been linked to mental and physical disorders (Ramezani et al, 2017 ) . In a study based on an econometric analysis, hunger correlated with “worsening health” in a cohort of South Africans ( Nwosu et al, 2022 ) .…”
Section: Discussionsupporting
confidence: 71%
“…However, the literature on this topic is scarce. While previous studies demonstrated the consequences of food insecurity among preschool teachers ( 12 , 13 ), few assessed food-related needs among elementary schools serving racial and ethnic minority populations with low income, particularly during the COVID-19 pandemic. The purpose of our study was to describe the prevalence of food insecurity and other social determinants of health, including financial stability, employment concerns, housing, transportation, childcare, and access to health care, during the initial phase of the COVID-19 pandemic among teachers in public schools serving racial and ethnic minority families with low incomes in the US.…”
Section: Introductionmentioning
confidence: 99%